Author and audience in Vitruvius' De architectura - Nichols, Marden Fitzpatrick, 1981- (Cambridge : Cambridge University Press, 2017)
Vitruvius' 'De architectura' is the only extant classical text on architecture whose impact on Renaissance masters, including Leonardo da Vinci, is well known. But what was the text's purpose in its own time (c.20s BCE)? In this book, Marden Fitzpatrick Nichols reveals how Vitruvius pitched the Greek discipline of architecture to his elite Roman readers, most of whom were undoubtedly laymen. The inaccuracy of Vitruvius' architectural rules, when compared with surviving ancient buildings, has knocked him off his pedestal. Nichols argues that the author never intended to provide an accurate view of contemporary buildings. Instead, Vitruvius crafted his authorial persona and remarks on architecture to appeal to elites (and would-be elites) eager to secure their positions within an expanding empire. This is the first analysis of 'De architectura' from archaeological and literary perspectives. Vitruvius emerges as a knowing critic of a social landscape in which the house made the man.
Greek knowledge and the Roman world -- The self-fashioning of scribes -- House and man -- Art display and strategies of persuasion -- The vermilion walls of Faberius scriba.
Revision of the author's thesis (university of cambridge, 2009) under the title: vitruvius and the rhetoric of display: wall painting, domestic architecture and roman self-fashioning.
Includes bibliographical references (pages 195-223) and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Vitruvius Pollio. -- Criticism, Textual; De architectura (Vitruvius Pollio); Authors and readers -- Rome; Architecture and society -- Rome; Écrivains et lecteurs -- Rome; Architecture et société -- Rome; ARCHITECTURE -- Adaptive Reuse & Renovation; ARCHITECTURE -- Buildings -- Landmarks & Monuments; ARCHITECTURE -- Professional Practice; ARCHITECTURE -- Reference; Architecture and society; Authors and readers; Rome (Empire); Electronic books; Criticism, interpretation, etc